Acute Myeloid Leukemia Presenting with Pulmonary Tuberculosis. (28th May 2014) - Thomas, Merlin; AlGherbawe, Mushtak
Abstract : We report the case of a 58-year-old immunocompetent man presenting with fever, cough, anorexia, weight loss, and cervical lymphadenopathy. Blood investigations revealed severe neutropenia with monocytosis. Chest imaging showed bilateral reticular infiltrates with mediastinal widening. Bronchoalveolar lavage culture and molecular test were positive for Mycobacterium tuberculosis and treatment with isoniazid, rifampicin, pyrazinamide, and ethambutol was started. Although pulmonary tuberculosis could explain this clinical presentation we suspected associated blood dyscrasias in view of significant monocytosis and mild splenomegaly. Bone marrow aspiration revealed acute myeloid leukemia. Thereafter the patient received induction chemotherapy and continued antituberculous treatment. After first induction of chemotherapy patient was in remission and successfully completed 6 months antituberculosis therapy without any complications. To our knowledge there has been no such case reported from the State of Qatar to date.